2017
DOI: 10.1507/endocrj.ej16-0521
|View full text |Cite
|
Sign up to set email alerts
|

A positive family history of hypertension might be associated with an accelerated onset of type 2 diabetes: Results from the National Center Diabetes Database (NCDD-02)

Abstract: Abstract. Type 2 diabetes, which is characterized by a combination of decreased insulin secretion and decreased insulin sensitivity, can be delayed or prevented by healthy lifestyle behaviors. Therefore, it is important that the population in general understands their personal risk at an early age to reduce their chances of ever developing the disease. A family history of hypertension is known to be associated with insulin resistance, but the effect of a family history of hypertension on the onset of type 2 di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 30 publications
(30 reference statements)
0
7
0
Order By: Relevance
“…The present study identified twelve national clinical diabetes registries spread over four different continents, mostly concentrated in the Northern part of Europe [13,14,57,[65][66][67][68][69][70][71][72]. Altogether, these databases comprised a total of 7,181,356 diabetic patients.…”
Section: Discussionmentioning
confidence: 99%
“…The present study identified twelve national clinical diabetes registries spread over four different continents, mostly concentrated in the Northern part of Europe [13,14,57,[65][66][67][68][69][70][71][72]. Altogether, these databases comprised a total of 7,181,356 diabetic patients.…”
Section: Discussionmentioning
confidence: 99%
“…Due to the high costs and low cooperation rate among patients, family history was regarded as a direct or indirect interpretation of inheritable risk factor which helps clinicians to evaluate the risk for DR. It is reported that presence of family history, diabetes, and hypertension, always indicated lower age of the patients which is associated to rather longer duration of diabetes for these patients [6,7]. In addition, researches revealed a family history of diabetes and hypertension also contributed to a higher frequency of DR [8,9].…”
Section: Introductionmentioning
confidence: 95%
“…Journal of Diabetes Research risk of diabetes and speeds up diabetes occurrence. A retrospective study conducted on 1299 patients revealed that patients with a family history of hypertension develop diabetes mellitus two years earlier than those without a family history [32]. Obesity was the other factor that had a statistically significant connection.…”
Section: Discussionmentioning
confidence: 99%